Ekstraksi dan Uji Stabilitas Antosianin dari Kulit Buah Naga Super Merah (Hylocereus costaricensis) - Endang Kwartiningsih; Agatha Prastika K; Dian Lellis Triana (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Natural food colorant is better for our healthrather than synthetic food colorant. Based on that case, natural colorant is recommended. The natural colorant is potential to be extracted as anthocyanin from super red dragon fruit (Hylocereus costaricensis) peel.Super red dragon fruit has been processed to be food products such as syrup, cup drink, fermented drink, etc, but its peel generates waste.However, the peel contains of anthocyanin as an antioxidant that can be used for nutraceuticals. This research consisted of two steps. The first step was to determine optimum condition for the anthocyanin extraction from super red dragon fruit peel such as the variation of solvent, temperature, ratio of super red dragon fruit peel and solvent. The second step was to test the stability of anthocyanin at various pH, heating, oxidator, storage condition,sunlight exposure. Anthocyanin was extracted using batch extraction. The optimum variables were achieved at aquadest as solvent, 50oC, ratio substance and solvent 1:6 for 70 minutes extraction time.The anthocyanin extract from super red dragon fruit peel was stable at pH 4 and low temperature (10oC) storage. Red colorant from super red dragon fruit peel extract was not stable of heating, contacting with oxidator H2O2, and sunlighting exposure